2010
DOI: 10.1074/jbc.m109.089631
|View full text |Cite
|
Sign up to set email alerts
|

Cytosines, but Not Purines, Determine Recombination Activating Gene (RAG)-induced Breaks on Heteroduplex DNA Structures

Abstract: The sequence specificity of the recombination activating gene (RAG) complex during V(D)J recombination has been well studied. RAGs can also act as structure-specific nuclease; however, little is known about the mechanism of its action. Here, we show that in addition to DNA structure, sequence dictates the pattern and efficiency of RAG cleavage on altered DNA structures. Cytosine nucleotides are preferentially nicked by RAGs when present at single-stranded regions of heteroduplex DNA. Although unpaired thymine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 56 publications
4
60
0
Order By: Relevance
“…RAG Expression and Purification-Human GST and MBP core RAG1 (384 -1008 amino acids; cRAG1) and core RAG2 (1-383 amino acids; cRAG2) proteins were purified as described (35,36). The protein expression was checked by Western blotting by using the appropriate antibodies (Santa Cruz Biotechnology) (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAG Expression and Purification-Human GST and MBP core RAG1 (384 -1008 amino acids; cRAG1) and core RAG2 (1-383 amino acids; cRAG2) proteins were purified as described (35,36). The protein expression was checked by Western blotting by using the appropriate antibodies (Santa Cruz Biotechnology) (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The double-strand break thus generated is a prerequisite for chromosomal translocations. Another RAG-mediated mechanism in translocations utilizes the novel property of RAGs being a structure-specific nuclease (33)(34)(35)(36). It has been shown that a non-B DNA structure formed at BCL2 MBR could be cleaved by RAGs, leading to t(14;18) translocation (3,33,37).…”
mentioning
confidence: 99%
“…It has been shown that RAGs can cleave different altered DNA structures or end configurations in physiological ionic conditions [11][12][13][14][15][16][17]. Besides, RAGs can also cleave hairpin structures in the presence of Mn 2+ [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cytosine and thymine at the single-stranded (ss) region of heteroduplex DNA is critical for RAG nicking and double-strand break formation [12]. A minimum of two cytosines at the ss region of heteroduplex DNA is required for efficient RAG cleavage [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation